Hubungan Antara Konsep Diri Dengan Komunikasi Interpersonal Pada Mahasiswa Yang Berasal Dari Provinsi X - GIRI, RO'IZ SANTRIA (2016)
The Correlation between The Self-Concept and The Interpersonal Communication in The University Students Coming from Province X Ro'iz Santria Giri Susatyo Yuwono Psychology Faculty, Muhammadiyah University of Surakarta Roizsantriagiri@gmail.com ABSTRACT The human life is never apart from the needs to get along with fellows. This need is one of the basic needs for human. Because of the presence of the needs, human will conduct an interaction with their fellows to reach a certain goal. Interaction among human beings can be conducted through communication. The self-concept is a very determinant factor in the interpersonal communication, because each person behaves as appropriate as possible to his/her self-concept. The objectives of this research were to know the correlation between the Self-Concept and the Interpersonal Communication, the effective contribution of the Self-Concept to the Interpersonal Communication, the Level of the Self-Concept, and the Interpersonal Communication. The subjects of this research were 109 university students who stayed in the Dormitory of university students of Province X Wisma X located in Sleman D.I. Yogyakarta. The method of sampling in this research used the kind of incidental sampling. The method of data collection used a quantitative approach with the measurement of the scale of self-concept and the scale of interpersonal communication. The technique data analysis used in this research was the Pearson Product Moment Correlation using the aid of program SPSS 16 For Windows. Based on the results of the data analysis, it was obtained the coefficient of correlation 0.539 with sig = 0.000; (p < 0.001) that meant that there was a very positively significant correlation between the self-concept and the interpersonal communication in the university students coming from Province X. The effective contribution or the role of self-concept on the interpersonal communication was as much as 29.1%, the rest 70.9% was influenced by other factors. The variable of interpersonal communication has the empirical mean as much as 75.51, therefore, it was categorized as moderate, meanwhile, the variable of self-concept was known having the empirical mean as much as 105,75, therefore, it was categorized as high. Keywords: Self-concept, Interpersonal communication